Analysis of Bacteria Escherichia coli, Salmonella sp and Shigella sp on Black Sticky Rice Ice in Malang - Alvina Via Denita; Ainur Rofieq; H Husamah; Abdulkadir Rahardjanto (Universitas Wiralodra, 2022)
Es tape ketan hitam is a traditional drink that is in great demand by the public and has the potential as a source of disease transmission is in the process of processing not using proper hygiene sanitation. The purpose of this research is to determine the content of Escherichia coli, Salmonella sp., and Shigella sp. in es tape ketan hitam. The research was conducted by planting Escherichia coli on EMBA and planting Salmonella sp., and Shigella sp. on SSA. The technique used is the spread method. The results of this study indicate that samples 1, 2, 5 and, 6 contain Escherichia coli exceeding the threshold. Samples 1, 5 and, 6 contained Salmonella sp., and Shigella sp. exceed the provisions. Microbiological requirements of drinks based on PerBPOM RI No. 13 of 2019 is the maximum total Escherichia coli, which is < 3 colonies/ml and 0 colonies/25ml (negative) for Salmonella sp., and Shigella sp. So it can be concluded that 4 out of 6 samples of es tape ketan hitam in Malang City do not meet the criteria for a drink that is fit for consumption based on PerBPOM RI No. 13 of 2019.